ROOM SEARCHING APPLICATION IN HOTEL RESERVATION SYSTEM BY USING EVERYDAY LANGUAGE INTERFACE - Hernawan Sulistyanto; - Nurgiyatna (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
This study was aimed at creating a prototype of the hotel reservation system with colloquial interface. An input provided by the prospective hotel guests which form a sentence using colloquial language. Indonesian language will be used to query the data of rooms that is stored in a hotel data base. The performance of reservation system relies heavily on a wealth of knowledge and data held by the system. The output of the system is room information in accordance with the given query by the potential guests. The existence of this room searching model with colloquial interface is expected to be an alternative to the hotel reservation service in order to provide a more ﬂ exible system in the interaction with the guests.